Evaluasi Usabilitas Dan Rekomendasi Desain Antarmuka Website Kesehatan (Studi Kasus: Hellosehat.Com) - Pasaribu, Paul Ronaldo Yonathan; Suwarno, Sri; Setiadi, Hendro (Institut Teknologi Telkom Purwokerto, 2023)
The Covid-19 pandemic is an encouragement for all people to be able to transform from previously having to meet face-to-face, forced by circumstances to turn into online meetings. All aspects of human life are forced to change, including in terms of health. In the current pandemic era, people are afraid to travel for treatment or even consult a doctor in person. With health websites such as hellosehat.com or other health websites, people can be helped to access health information. This health website can be an alternative for patients who have minor illnesses that do not need medical treatment or medical equipment assistance from the hospital. Therefore, a website interface that is easy to understand by users is needed so as not to be confused when accessing and using the website. This study aims to evaluate the interfaces of existing health sites. In this case study, researchers used hellosehat.com site to evaluate. The method used in this study is the goal directed design method, where in this method there are six steps, namely research, modelling, requirements, framework, refinement, and support. The development of hellosehat.com site using the goal directed design method resulted in an increase in usability, namely effectiveness which increased from 62.22% to 97.78%, which was an increase of 35%. In the efficiency factor, there was an increase of 44%, where in the initial test it scored 49.88% increasing to 94.77%. In the satisfaction factor, there was an increase of 26%, from 65% to 91.25%.